Dissemination of a Clone of Unusual Phenotype of Pandrug-Resistant Acinetobacter baumannii at a University Hospital in Taiwan - Kuo, Lu-Cheng (American Society for Microbiology, 2004)
From December 2002 to February 2003, 15 isolates of pandrug-resistant unidentified Acinetobacter species were recovered from seven patients treated on different wards or intensive care units. Both 16S-23S rRNA intergenic spacer PCR-restriction fragment length polymorphism profiles and sequence analysis of these isolates identified them as Acinetobacter baumannii. This pandrug-resistant A. baumannii strain with an unusual phenotype could persist in humans for long periods and was widely disseminated throughout the hospital.